2015
DOI: 10.1038/srep13755
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Antibody Responses by the Histone H2A Deubiquitinase MYSM1

Abstract: B cell-mediated antibody response plays critical roles in protective immunity, as well as in the pathogenesis of allergic and autoimmune diseases. Epigenetic histone and DNA modifications regulate gene transcription and immunity; however, so far, little is known about the role of epigenetic regulation in antibody responses. In this study, we found that mice deficient in the histone H2A deubiquitinase MYSM1, despite their severe defect in B cell development, exhibit an enhanced antibody response against both T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…13, 14, 15, 16, 17 Our previous work revealed critical roles of Mysm1-mediated H2A deubiquitination in HSC differentiation, 16 NK cell maturation, 14 and B-cell and dendritic cell (DC) commitments. 13, 18 We found that Mysm1 −/− impairs self-renewal and lineage reconstitution of HSC by abolishing recruitment of key transcriptional factors to the Gfi-1 locus. 16 In the present study, we further investigated the role of Mysm1 in the maintenance of cell lineages by systematically analyzing the impact of Mysm1 deficiency on T-cell lineages.…”
mentioning
confidence: 79%
“…13, 14, 15, 16, 17 Our previous work revealed critical roles of Mysm1-mediated H2A deubiquitination in HSC differentiation, 16 NK cell maturation, 14 and B-cell and dendritic cell (DC) commitments. 13, 18 We found that Mysm1 −/− impairs self-renewal and lineage reconstitution of HSC by abolishing recruitment of key transcriptional factors to the Gfi-1 locus. 16 In the present study, we further investigated the role of Mysm1 in the maintenance of cell lineages by systematically analyzing the impact of Mysm1 deficiency on T-cell lineages.…”
mentioning
confidence: 79%
“…These studies elucidated the role of MYSM1 in the de-repression of a range of genes essential for normal stem cell differentiation and lineage specification in hematopoiesis. The genes de-repressed by MYSM1 include: Ebf1 in B cell progenitors [20], Pax5 in naïve B cells [30], miR150 in B1a cells [31], Id2 in NK cell progenitors [32], Flt3 in dendritic cell precursors [33], and Gfi1 in hematopoietic stem and progenitor cells [34] (Figure 2). At many of these loci, loss of MYSM1 resulted in increased binding of PRC1 complex proteins and elevated levels of histone H2AK119ub [20,30,[32][33][34], suggesting that MYSM1 antagonizes PRC1-mediated histone ubiquitination and transcriptional repression.…”
Section: Mysm1 Is a Transcriptional Regulator In Hematopoietic Lineagmentioning
confidence: 99%
“…Increased levels of histone H3K27me3 were also observed at several loci [20,30,33,34], suggesting indirect cross-talk between MYSM1-deficiency and PRC2 complex activity. Regrettably, only a few studies specifically tested whether the catalytic activity of MYSM1 is essential for its transcriptional activity [7].…”
Section: Mysm1 Is a Transcriptional Regulator In Hematopoietic Lineagmentioning
confidence: 99%
See 2 more Smart Citations